HIV status defines distinct immunological drivers of persistent portal hypertension after HCV cure in people with advanced cirrhosis - Martín-Escolano, Rubén; Fernández-Rodríguez, Amanda; Tarancon-Diez, Laura; Berenguer, Juan; Codina, Helena; Amigot-Sánchez, Rafael; González-García, Juan; Hontañón, Víctor; Pérez-Latorre, Leire; Ibañez-Samaniego, Luis; Llop-Herrera, Elba; Olveira, Antonio; et al. (Frontiers in Immunology, 2026)
IntroductionThe immunological drivers of portal hypertension regression after hepatitis C virus (HCV) cure are poorly understood, particularly in the context of human immunodeficiency virus (HIV) coinfection We aimed to identify baseline immune signatures predicting the evolution of the hepatic venous pressure gradient (HVPG) in people with and without HIV (PWH/PWoH).MethodsWe prospectively followed 41 individuals with advanced cirrhosis (18 PWoH, 23 PWH) who were cured of HCV with direct-acting antivirals (DAA). Baseline plasma and cellular immune markers were extensively profiled using multiplex assays and flow cytometry. We used mixed-effects modeling to test for associations between these baseline immune features and the change in HVPG over a 48-week follow-up period, with q-values controlling for false discoveries.ResultsTwo distinct immunological profiles of impaired HVPG regression emerged. In PWoH, impaired regression was linked to a broad proinflammatory profile [TNF-α (AMR = 1.13; q=0.012), IL17A (AMR = 1.28; q=0.012), and IL10 (AMR = 1.2; q=0.028)], a widespread total CD4+ T-cell activation [HLA-DR+ (AMR = 1.44; q<0.001) and CD38+HLA-DR+ (AMR = 1.3; q=0.007)], and robust activation across central memory (CM) and effector memory (EM) subsets. Conversely, in PWH, impaired HVPG regression was associated with sVCAM-1 (AMR = 1.58; q=0.096), and a more focused activation within EM (HLA-DR+, AMR = 1.08; q=0.030) and TemRA (CD38+HLA-DR+, AMR = 1.12; q=0.030) CD4+ T-cells.DiscussionHIV coinfection fundamentally reshapes the immunological landscape of post-cure portal hypertension recovery. The shift from systemic inflammation in PWoH to endothelial dysfunction and T-cell exhaustion in PWH reveals distinct pathological pathways. Understanding these signatures is a crucial step toward developing targeted therapies to promote complete hepatic recovery.